Pengaruh Campuran Feses Sapi Potong dan Feses Kuda Pada Proses Pengomposan Terhadap Kualitas Kompos - Hidayati, Yuli Astuti; Marlina, Eulis Tanti; Benito AK, Tb; Harlia, Ellin (Fakultas Peternakan Universitas Jambi, 2010)
This study aims to determine compost quality (content of N, P2O5, K2O) generated from various mixtures of beef cattle feces and the feces of horses. The method used in this study is the experimental method in the laboratory using a completely randomized design with 3 treatments, ie P1 = C / N ratio of 25, P2 = C / N ratio of 30 and P3 = C / N ratio of 35 and replications 6 times. To determine the effect of treatments, data were analyzed with ANOVA and Duncan test. The results showed that the mixture of feces of beef cattle and horse feces with various C / N ratio did not significantly affect the quality of compost. N content in compost produced = 0.7867 to 0.8000%, P2O5 content = 0.5883 to 0.6000%, K2O = 0.5733 to 0.5883%